OTOMATISASI PLTMH UNTUK MENSTABILKAN TEGANGAN DAN FREKUENSI DENGAN PENGATURAN GUIDE VANE DAN KAPASITOR EKSITASI BERDASARKAN PENGUKURAN ARUS BEBAN - Ta'Ali
Nowadays, the electric energy has already become a basic need for both industrial and household. Together with the rapid development of science and technology, the availability of electric energy resource also become to very urgent. West Sumatra region is geographically situated by the range of Bukit Barisan, so that as largely part of that is the isolated villages that far away from the range of PLN. The isolated villages are generally located at rivers streams or at the vicinity of the wall resources. The electric generating that suitable to the region is the Micro Hydro Power Electric Generating (MHPG). Unfortunately the MHPG currently operated at such region (Â±22 units) not yet has an automation system, so that the role of operators is still highly expected. One of the disadvantages is the operator\'s neglect that frequently results in the damage of the system. One of the attempts for improving efficiency and expanding the life of the system is an automation system. Generally, the operation of MHPG use an Induction Motor As Generators (IMAG). The stability of frequency and voltage it use carried out both by positioning the guide vane in adjusting the water flow entering into the turbine and the adjustment of excitation capacitor of IMAG. The research is implementing the automation system to stabilize the frequency and voltage the guide vane and the adjustment of, excitation capacitor of IMAG. The prototype are using current sensor module, frequency sensor, analog to digital converter (ADC), Programmable Parallel Interface (PPI), actuators control, and Personal Computer used as Central Processing Unit. The result of experimental test in the field for the prototype made shows the voltage regulation of the MHPG is of 5%, where as the frequency regulation is of 2%. in the various loads. Although the mechanical response to the power stability for load change is relatively slow, but the entirely this automation system of MHPG is sufficient for a basic need in a partly isolated villages.